Associations between blood eosinophils and decline in lung function among adults with and without asthma - Hancox, RJ; Pavord, ID; Sears, MR (European Respiratory Society, 2018)
Eosinophilic inflammation and airway remodelling are characteristic features of asthma, but the association between them is unclear. We assessed associations between blood eosinophils and lung function decline in a population-based cohort of young adults. We used linear mixed models to analyse associations between blood eosinophils and spirometry at 21, 26, 32 and 38 years adjusting for sex, smoking, asthma and spirometry at age 18 years. We further analysed associations between mean eosinophil counts and changes in spirometry from ages 21 to 38 years. Higher eosinophils were associated with lower forced expiratory volume in 1 s (FEV1)/forced vital capacity (FVC) ratios and lower FEV1 % predicted values for both pre- and post-bronchodilator spirometry (all p-values ≤0.048). Although eosinophil counts were higher in participants with asthma, the associations between eosinophils and spirometry were similar among participants without asthma or wheeze. Participants with mean eosinophil counts >0.4×109 cells·L−1 between 21 and 38 years had greater declines in FEV1/FVC ratios (difference 1.8%, 95% CI 0.7–2.9%; p=0.001) and FEV1 values (difference 3.4% pred, 95% CI 1.5–5.4% pred); p=0.001) than those with lower counts. Blood eosinophils are associated with airflow obstruction and enhanced decline in lung function, independently of asthma and smoking. Eosinophilia is a risk factor for airflow obstruction even in those without symptoms.